Вплив інвестиційної активності на обсяги будівельних робіт в Україні - Бєлєнкова, О. Ю. (Ways to Improve Construction Efficiency, 2013)
The article investigates the influence of different sources of financing investment in the growth of the construction work. Created equations allow to forecast and evaluation of the impact of funds allocated in fixed capital the volume of construction.